REKONSTRUKSI PARADIGMA KEPEMIMPINAN MADRASAH DALAM TRANSFORMASI KEARSIPAN DIGITAL - Abda Putra Erlangga; Nasyifa Zahra Nurafni; Rahmat Septiono; Sindi Afriza Najwa; Siswadi (STKIP Subang, 2026)
ABSTRACT The digital transformation of archival management has brought fundamental changes to educational administrative practices, including in madrasah institutions. Madrasah leadership is required not only to adapt to technological advancements but also to reconstruct leadership paradigms that are relevant to the demands of the digital era. This study aims to analyze and reconstruct the paradigm of madrasah leadership in the context of digital archival transformation using a qualitative approach with a literature review method. Data were collected from various scientific sources such as journals, books, and relevant policy documents. The findings indicate that digital archival transformation requires a shift from conventional administrative leadership toward transformational, collaborative, and technology-based leadership. Effective madrasah leadership in the digital era is characterized by the ability to integrate information technology, build a digital culture, and enhance accountability and transparency in archival management. Furthermore, the reconstruction of leadership paradigms includes strengthening digital literacy, organizational innovation, and data-driven decision-making. Therefore, madrasah leadership plays a strategic role in ensuring the success of digital archival transformation as part of improving educational governance quality. Keywords: madrasah leadership, digital archiving, digital transformation, leadership paradigm, literature study